Investigation into potential TEC changes due to 9 seismic tremors of 2021–2022 - YADAV, Kunvar S.; VADNATHANI, Rakesh B.; BHOYA, Mangesh D.; GOSWAMI, Keyurgiri R. (Contributions to Geophysics and Geodesy, 2025)
This research document delves into the analysis of alterations in Total Electron Content (TEC) as identified through GPS observations leading up to nine earthquakes that transpired between the late months of 2021 and 2022. The comprehensive study investigates the TEC variations and provides a detailed examination of heat maps centred around the earthquake epicentres. These heat maps, characterized by diverse latitudes and longitudes, play a pivotal role in validating the precise locations of the earthquake epicentres. Notably, the examination of these maps unveils discernible GPS TEC variations several days before the occurrence of each earthquake. In addition to the TEC analysis, the research sheds light on the fluctuations in solar magnetic parameters. The study elucidates instances where TEC peaks surpassed normal values, particularly during periods characterized by minimal solar radiation effects. This correlation between solar magnetic parameters and TEC fluctuations adds a nuanced layer to the understanding of the complex interplay of factors leading to seismic events. The cumulative findings derived from the investigation point towards a compelling conclusion: GPS TEC observations and the analysis of heat maps serve as indispensable indicators for identifying precursory signs that precede an impending earthquake. This multidimensional approach enhances our comprehension of the temporal and spatial aspects of seismic activity and underscores the potential significance of solar magnetic parameters in influencing such geophysical events.